(untitled) (Legal journal - Research in Legal and Social Sciences, 2017)
By Law No. 4083/2011, the Program for the Support and Protection of Witnesses and Victims in Criminal Proceedings was created in Paraguay, with the purpose of applying protection measures aimed at those who may be in a situation of risk or danger to life, physical integrity, freedom and security as a result of their intervention in a criminal proceeding. Thus, the State Attorney General’s Office has been designated as the enforcement authority through a Directorate hierarchically dependent on the State Attorney General since, by constitutional and legal mandate, the Public Ministry is the autonomous body that prosecutes the punishable act, which has in charge of the exercise of public criminal action and the corresponding evidentiary contribution, applying the necessary protection measures in transcendental criminal proceedings, in an effort to facilitate access to justice and promote its achievement. With the implementation of this program, the Government intends to strengthen the fight against organized crime, access to justice and combat corruption.